In vivo characterization of microglial engulfment of dying neurons in the zebrafish spinal cord - Morsch, Marco; Radford, Rowan; Lee, Albert; Don, Emily K.; Badrock, Andrew P.; Hall, Thomas E.; Cole, Nicholas J.; Chung, Roger (Frontiers in Cellular Neuroscience, 2015)
Microglia are specialized phagocytes in the vertebrate central nervous system (CNS). As the resident immune cells of the CNS they play an important role in the removal of dying neurons during both development and in several neuronal pathologies. Microglia have been shown to prevent the diffusion of damaging degradation products of dying neurons by engulfment and ingestion. Here we describe a live imaging approach that uses UV laser ablation to selectively stress and kill spinal neurons and visualize the clearance of neuronal remnants by microglia in the zebrafish spinal cord. In vivo imaging confirmed the motile nature of microglia within the uninjured spinal cord. However, selective neuronal ablation triggered rapid activation of microglia, leading to phagocytic uptake of neuronal debris by microglia within 20-30 minutes. This process of microglial engulfment is highly dynamic, involving the extension of processes towards the lesion site and consequently the ingestion of the dying neuron. 3D rendering analysis of time-lapse recordings revealed the formation of phagosome-like structures in the activated microglia located at the site of neuronal ablation. This real-time representation of microglial phagocytosis in the living zebrafish spinal cord provides novel opportunity to study the mechanisms of microglia-mediated neuronal clearance.